Immunoprofiling of BRAFV600E in Precancerous and Cancerous Lesions of Breast by Immunohistochemistry and its Association with Clinicopathological Features - Simran Khan; Arvind Bhake; Sunita Vagha (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Breast carcinoma in women is one of the few causes of morbidity and mortality which concerns the health providers. The molecular basis of breast carcinoma in recent years has provided the insight for the genesis of carcinoma, the prognostic, and predictive utility for targeted therapies. Aim: A study has been planned with the aim to know immunoprofiling of BRAFV600E in precancerous and cancerous lesions of the breast by Immunohistochemistry (IHC) and its association with clinicopathological features. Materials and Methods: The subjects will be divided in two groups of 45 cases each: Precancerous breast lesions; and Invasive ductal carcinoma. The tissue of these cases will undergo IHC of BRAFV600E. The comparison of expression is to be brought out and the clinicopathological association of immunoexpression of BRAFV600E will also be studied.